Epidemiological surveys of Blastocystis spp. isolates from the Proto-Malay and Negrito tribes in Peninsular Malaysia / Syuhadaratul Aini Mohamat - Mohamat, Syuhadaratul Aini (2015)
Blastocystis spp. is an enteric protozoan which is most commonly isolated organism in parasitological surveys. The distribution of the Blastocystis spp. appeared to be global as the infection typically in developing, tropical and subtropical countries. Nevertheless, the transmission of this parasite to human beings is still controversial and varied among reports from different geographic regions. Therefore, the present study was conducted to evaluate the prevalence and risk factors that might be associated with Blastocystis spp. infection. A series of cross-sectional study were carried out among 289 individuals from the Proto-Malay (150) and the Negrito (139) tribes and took place in selected villages in Negeri Sembilan and Perak, Peninsular Malaysia. The socio-demographic data for each individual was provided by using pretested questionnaire. The fecal samples were subjected to microscopic examination using Wheatley's trichrome stain and formalin-ether sedimentation techniques. The laboratory diagnosed with the Blastocystis spp. indicated the prevalence was greater in Negritos as compared to Proto-Malays (21.6% vs.13.3%). Moreover, this findings showed decrease in increasing age as the distribution of the infection was highest in individuals less than 15 years old (19.8%) as compared to their counterparts. Higher prevalence was reported in females compared to males in the ratio of 1.2:1. The univariate and multivariate analyses showed that the risk of being infected by Blastocystis spp. among the Proto-Malay tribe was associated with drinking of untreated water (OR = 6.25; 95% CI = 1.52,25.70; p = 0.019) and human-to-human transmission (OR = 21.48; 95% CI = 6.70, 68.82; P < 0.001). Similar findings was found in the Negrito tribe where drinking of untreated water (OR = 2.79; 95% CI = 1.10, 7.03;p = 0.026) and human-to-human transmission (OR = 6.19, 95% CI = 2.55, 14.98; p < 0.001) were also found to be significant risk factors of blastocystosis. This was consistent with the results for the overall population. Substantially, Blastocystis spp. infection is a major public health concern among Orang Asli population in Malaysia. Further studies involved the molecular approaches are essential to identify the subtype of Blastocystis spp. that responsible for this infection. The current study discovered that the blastocystosis was communicable through waterborne and anthroponoses among two tribes. Thus, the intervention of government in supplying clean water and health screening were urgently needed in averting the spread of this peculiar parasite.